Alien fish species in open waters of India: Appearance, establishment and impacts - JOSHI, KRIPAL DATT; BASHEER, V S; KUMAR, ADITYA; SRIVASTAVA, SATYENDRA MOHAN; SAHU, VIKASH; LAL, KULDEEP K (The Indian Journal of Animal Sciences, 2021)
The diverse germplasms pool already available in the vast and varied water resources of India has potential to cater to the need of the fisheries and aquaculture sector, but introduction of fish species for different purposes is still continuing. The exotic fishes introduced into India for different purposes covers nearly 13.6% of total fish diversity. Due to wider tolerance limit and generalist nature, some alien fish species have acclimatised to diverse eco-climatic conditions. Some of these introduced fishes are now established in the open water bodies including rivers, wetlands and reservoirs and some others are in the process of establishment. Degraded open waters and wanton destruction of fishery resources in the rivers have resulted in depletion of the sensitive fish species and appearance of exotic fishes. The potential risk areas for appearance of the alien species are mushrooming fish culture units in different parts of the country, porous boundaries, farming of alien fishes in flood prone areas, rapid expansion of aquaculture and ornamental fish trade. Eradication of an introduced species is usually difficult or impossible once it is established in open water bodies. Therefore, there is an urgent need to regulate the import of alien fish species, based on their merit and likely impacts on open waters.